Producer Strategy in Distribution of Yogyakarta Special Fund Documentary Film “YK48” - Basri, Azzahra Silvia; Arifianto, Budi Dwi (Jogjakarta Communication Conference (JCC), 2025)
Documentary films face challenges in distribution, especially in reaching a wider audience. This study analyzes the distribution strategy of the documentary film